2009
DOI: 10.1111/j.1365-3121.2009.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground displacement data around the city of Ravenna do not support uplifting Venice by water injection

Abstract: The proposed injection of seawater in a brackish, sandy aquifer\ud lying 600–800 m under the lagoon of Venice to lift Venice itself\ud uniformly up to 30 cm in 10 years raises many problems. We\ud discuss here whether a smooth uplift can be obtained as\ud claimed by the proponents. We first underline the similarities\ud between the Ravenna and Venice case. We then examine the\ud subsidence around Ravenna because of fluid extraction and the\ud measured surface displacements for the period when there is\ud press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Natural subsi-dence has been estimated at 1 -2 mm/year in the Delta. Reclamation has also caused local subsidence, but cannot completely explain the falling rates over the last 60 years [38]- [44].…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
See 2 more Smart Citations
“…Natural subsi-dence has been estimated at 1 -2 mm/year in the Delta. Reclamation has also caused local subsidence, but cannot completely explain the falling rates over the last 60 years [38]- [44].…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
“…Due to the significant economic impact of subsidence, vertical movements have been monitored since 1950 [45] by repeated high-precision leveling, undertaken by the IGMI (Istituto Geografico Militare Italiano) and later by other local authorities, companies and institutions [22] [39] [44] [46]- [49]. Caputo et al [39] and Borgia et al [47] reported a maximum subsidence rate of 250 mm/year in the central part of the Po Delta for the period 1951-1957 and 180 mm/year between 1958 and 1962.…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some concerns on the uniformity of the predicted uplift have been raised (Schrefler et al. , 2009) by comparison with the land settlement experienced at Ravenna, a town 120 km south of Venice, where extensive joint gas and groundwater withdrawals have caused a large non‐uniform subsidence during the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…According to Comerlati et al (2004) this solution might raise the city of Venice by 25-30 cm in 10 years. However, the level of risk of major damage to city structure and buildings due to uneven land uplifting is matter of scientific debate (see for example, Gambolati 2009;Schrefler et al 2009). …”
Section: Structural Measures and Sea-level Risementioning
confidence: 99%